ANALYSIS OF OPPORTUNITIES FOR VAT REFORMING IN UKRAINE - Sierbin , Vadym (Socio-economic relations in the digital society, 2021)
Abstract. Ukraine’s independence has become a positive factor in the development of democratic tendencies in our country and has also significantly changed the economic sector. It is still in the process of being sought and reformed. In this context, the solution to the problem of improving the tax system is particularly clear, as the old model of planned economy was unacceptable, and the economic vector has changed from command to marketing, where international standards of accounting and taxation are actively implemented. At the same time, today the urgent task of the evolution of the tax system in Ukraine is still to ensure its stability and easy correction, which in turn should lead to some positive factors: increased budget revenues, improved mechanisms for collecting and managing value added tax. The article considers the nature and current state of value added tax in Ukraine and the world. It is established that the value added tax is one of the most important taxes. The main provisions of the legislation concerning the function of value added tax and the main issues related to the collection and administration of taxes are identified. It has been identified that the various aspects of value added tax reform are interlinked, and that existing methods are not effective enough. As a result, the main problems of modern value added tax management are the underestimation of the economic components of the tax system, complex mechanisms and non-transparent payment systems, which create preconditions for insufficient funding of the country and contribute to corruption. The possibility and direction of VAT reform in Ukraine are clearly outlined and proposed. Among the main ways to reform VAT, special attention is paid to reducing the value added tax rate, which should lead to lower domestic product prices and increased demand. Simplification of the rules for collecting and paying VAT, which in turn will help solve problems related to VAT administration. As a result, businesses will receive additional funds, which they are currently forced to use to attract additional specialists in the legal and financial fields, inspections, court fees, meetings of fiscal authorities, etc. The released resources (and related funds) will increase the profitability of companies and can be used for further development of specific organizations, which in turn will increase their profitability and, consequently, increase revenues from value added tax. Keywords: value added tax, VAT, state budget, administration, indirect taxes, reform. JEL Classification H61, H25 Formulas: 0; fig.: 2; tabl.: 1; bibl.: 9.